“The Sort of Story That Has You Covering Your Mirrors” - Jeffrey Tolbert (Semiotic Review)
As a monster, Slender Man epitomizes the simultaneous alienness and familiarity that characterizes the uncanny. Created by users on the Something Awful forums, the Slender Man’s most common depiction is as a preternaturally tall, skinny humanoid with a white, faceless head, dressed incongruously—given his tendency to lurk in forests—in a black business suit and tie. A potent symbol of fear, Slender Man simultaneously serves as a flexible rhetorical tool, used variously to critique popular trends, instill fear in its audiences, and as a self-referential “in-joke” whose significance is only intelligible to those already familiar with the phenomenon itself. Thus the figure of the Slender Man indexes at least two separate intellectual strands, two distinct but related conceptual frameworks: first, Slender Man is a sign of abject fear—the ultimate Other, the final evolution of radical alterity. Secondly, Slender Man subtly references the self-conscious communicative processes that gave rise to the tradition itself and are, in fact, the reason for its continued existence as an internet icon. The purpose of this article is to demonstrate how, as an iconic figure produced through a collective effort and deliberately modeled after an existing and familiar folklore genre, Slender Man represents what might be thought of as reverse ostension. Building on folkloristic work on the concept of ostension, the Slender Man mythos is shown to encapsulate important semiotic processes that are self-consciously employed by its creators to make a new narrative tradition that deliberately mimics established ones.